PERAN NILAI PERUSAHAAN DALAM MENENTUKAN PENGARUH KINERJA PERUSAHAAN TERHADAP FINANCIAL DISTRESS DI ASEAN - Dian Oktarina (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
The trade war between China and the United States has an impact on the world economic turmoil that caused all countries in the world including the countries in ASEAN which are mostly including developing countries, especially Indonesia, also experiencing economic difficulties. This is indicated by the deficit of the transaction balance in Indonesia of two billion rupiahs. The occurrence of this turmoil will certainly also affect companies in ASEAN countries which if not addressed will experience financial difficulties that could lead to bankruptcy. This study aims to see how the company's performance can increase the value of the company so as to prevent the company from experiencing financial distress. This study uses samples from manufacturing companies listed on stock exchanges in five ASEAN countries, namely Indonesia, Malaysia, Singapore, the Philippines, and Thailand. This study uses quantitative analysis methods with technical analysis of descriptive statistics, multiple regression, and logistic regression. The results showed that company performance had a positive effect on firm value, the firm value had a positive effect on financial distress, and company performance negatively affected financial distress. Mediation test results show that the company's value cannot mediate between the company's performances against financial distress.